2014
DOI: 10.1097/tp.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Single-Donor Islet Transplantation and Long-term Insulin Independence in Select Patients With Type 1 Diabetes Mellitus

Abstract: We have identified clinically relevant differences defining the achievement of insulin independence after single-donor transplantation. Based on these differences, a preoperative insulin requirement of less than 0.6 U/kg per day and receiving more than 5,646 islet equivalents (IEQ)/kg have a sensitivity of 84% and 71% and specificity of 50% and 50%, respectively, for insulin independence after single-donor islet transplantation. With ideal patient selection, this finding could potentially increase single-donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 22 publications
(29 reference statements)
5
44
0
Order By: Relevance
“…is in line with the results of other groups (2,4,8,(17)(18)(19)(20)(21)(22)(23) which studied more heterogeneous groups of isletalone and islet-after-kidney transplantation recipients and/or using different immune suppression regimens.…”
Section: A C C E P T E Dsupporting
confidence: 77%
“…is in line with the results of other groups (2,4,8,(17)(18)(19)(20)(21)(22)(23) which studied more heterogeneous groups of isletalone and islet-after-kidney transplantation recipients and/or using different immune suppression regimens.…”
Section: A C C E P T E Dsupporting
confidence: 77%
“…In 2014, Shapiro group et al reported a significant association between single-donor islet transplantation and long-term insulin independence with older age and lower insulin requirements prior to transplantation (76). Moreover, higher weight and BMI of the donor resulted in a higher isolated islet mass and significant association with single-donor transplantation (76). The effectiveness of pre-transplant administration of insulin and heparin has been shown on achievement of insulin independence in single-donor islet transplantation (76).…”
Section: Improvement Of Pancreas Procurement Islet Isolation and Culmentioning
confidence: 99%
“…Moreover, higher weight and BMI of the donor resulted in a higher isolated islet mass and significant association with single-donor transplantation (76). The effectiveness of pre-transplant administration of insulin and heparin has been shown on achievement of insulin independence in single-donor islet transplantation (76).…”
Section: Improvement Of Pancreas Procurement Islet Isolation and Culmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish an islet population capable of producing enough insulin for clinical effect, a large number of these cells (>5,600 islet equivalents/kg) must be transplanted 9. Post-transplant, the C-peptide level is used as a marker for graft survival as its production often outlasts insulin independence and overall clinical effect of the transplant.…”
Section: Introductionmentioning
confidence: 99%